2016
DOI: 10.1080/13607863.2016.1168361
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal view of factors that influence the emotional well-being of family caregivers to individuals with heart failure

Abstract: Interventions should be offered based on caregivers' needs rather than patients' health outcomes, and should focus on fostering caregivers' feelings of personal gain, assisting them with securing social support, and engaging in valued activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 53 publications
4
31
0
Order By: Relevance
“…Other qualitative research has identified caregivers experience a reduction in social participation (Bulley, Shiels, Wilkie, & Salisbury, 2010) and loss of spontaneity and freedom (Bäckström & Sundin, 2009). Further, quantitative research suggests caregivers experiencing restrictions in working towards roles and goals of importance and value experience increased levels of depression (Grigorovich et al, 2016;Hwang, Rivas, Fremming, Rivas, & Crane, 2009;Mausbach et al, 2011;Rochette et al, 2007). Whilst some caregivers are able to re-engage with activities over time, those with higher levels of depression and caring for stroke survivors with greater illness severity are less likely to (Grigorovich et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other qualitative research has identified caregivers experience a reduction in social participation (Bulley, Shiels, Wilkie, & Salisbury, 2010) and loss of spontaneity and freedom (Bäckström & Sundin, 2009). Further, quantitative research suggests caregivers experiencing restrictions in working towards roles and goals of importance and value experience increased levels of depression (Grigorovich et al, 2016;Hwang, Rivas, Fremming, Rivas, & Crane, 2009;Mausbach et al, 2011;Rochette et al, 2007). Whilst some caregivers are able to re-engage with activities over time, those with higher levels of depression and caring for stroke survivors with greater illness severity are less likely to (Grigorovich et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Further, quantitative research suggests caregivers experiencing restrictions in working towards roles and goals of importance and value experience increased levels of depression (Grigorovich et al, 2016;Hwang, Rivas, Fremming, Rivas, & Crane, 2009;Mausbach et al, 2011;Rochette et al, 2007). Whilst some caregivers are able to re-engage with activities over time, those with higher levels of depression and caring for stroke survivors with greater illness severity are less likely to (Grigorovich et al, 2016). As such, an important finding emerging from this study is caregivers with elevated depressive and anxious symptoms may experience long-term difficulties in re-engaging with goals and roles of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Low health perception, care burden, distress, income state of the caregiver, providing care for 5 years and more, quality of life and sex of the caregiver, may affect the well‐being of the caregiver. Again, sex and age of the caretaker, cormorbidity, cognitive dysfunction, behavioural problems, depressive symptoms, chronic disease of older adults and symptoms associated with his/her disease may affect well‐being of the caregiver . For that reason, factors affecting health and well‐being of caregiving family members need to be determined and they need help and support for meeting their needs in order to maintain caregiving …”
Section: Introductionmentioning
confidence: 99%
“…A study showed that family member caregivers present musculoskeletal and sleep disorders, fatigue, increased levels of stress, anxiety and social isolation due to the care (provided) (2) . Worse quality of life (4) , depression (5) and increased burden (6) are other negative aspects found in family members.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that family member caregivers present musculoskeletal and sleep disorders, fatigue, increased levels of stress, anxiety and social isolation due to the care (provided) (2) . Worse quality of life (4) , depression (5) and increased burden (6) are other negative aspects found in family members.Negative experiences associated with time spent providing care may lead the caregiver to neglect their own health. A meta-analysis of 168 studies found that different impacts are experienced by spouses, children and stepchildren caregivers.…”
mentioning
confidence: 99%